FINANCIAL AND INVESTMENT ASPECTS OF STABILIZATION OF THE GEORGIAN ECONOMY IN THE CRISIS PERIOD - Malkhaz Bakradze (European Scientific Journal, ESJ, 2014)
The global economic crisis originated from the financial crisis when banks and financial institutions took the unreasonable high risks and mass bonuses in order to receive high profits. The author of these words is the President of the USA Barak Obama. Like worldwide, in Georgia the global financial crisis most of all effected the financial sector and became the basis for significant changes. The analysis of the few-year struggle against the results of the financial crisis shows several fundamental deficiencies of the existing international regulation framework and risk management practice and can impact potentially on any jurisdiction and bank system. Basel III document published by the Basel Committee on December 16, 2010 is just designed to eradicate such deficiencies. The financial crisis has also intensified the irregular reduction in leverage and existence of close relations between the institutes. The dynamics of procyclicality and system risks together with the particular risks typical for the banks shows the necessity of consideration of the aggregated risks of banking and financial sector in whole. The disagreed approach to the risks became the reason of the global crisis. The Group of Twenty will start to operate the new framework in 2013 and it will be introduced step by step until 2019. In spite of the transitional provisions, the introduction of Basel III is a very difficult task. According to McKinsey & Co. publication, Basel III will have significant impact on the European banking sector.